Consumer protection in Indonesian banking industry - Aryatie, Indira Retno; Mohd. Sulaiman, Aiman @ Nariman (2015)
The objective of the study is to assess the development of consumer protection in Indonesia, especially in banking industry. The study descriptively analyzes the legislations and institutions designed to protect the rights of consumers. The study identifies that consumer bank protection is a subset of the Indonesian banking system which developed based on set of banking laws such as Banking Act, Central Bank Act, Finance Services Authority Act and Deposit Insurance Corporation Act. Special need of Islamic banking consumers has been accommodated in the Islamic Banking Act. The reformation in laws and institutions provide better consumer protection in banking industry.